Molecular Ecology of Isoprene-Degrading Bacteria - Ornella Carrión; Terry J. McGenity; J. Colin Murrell (Microorganisms, 2020)
Isoprene is a highly abundant biogenic volatile organic compound (BVOC) that is emitted to the atmosphere in amounts approximating to those of methane. The effects that isoprene has on Earth’s climate are both significant and complex, however, unlike methane, very little is known about the biological degradation of this environmentally important trace gas. Here, we review the mechanisms by which bacteria catabolise isoprene, what is known about the diversity of isoprene degraders in the environment, and the molecular tools currently available to study their ecology. Specifically, we focus on the use of probes based on the gene encoding the α-subunit of isoprene monooxygenase, isoA, and DNA stable-isotope probing (DNA-SIP) alone or in combination with other cultivation-independent techniques to determine the abundance, diversity, and activity of isoprene degraders in the environment. These parameters are essential in order to evaluate how microbes might mitigate the effects of this important but neglected climate-active gas. We also suggest key aspects of isoprene metabolism that require further investigation in order to better understand the global isoprene biogeochemical cycle.